A retrospective, observational, real-world evidence study to understand the clinical and obstetric characteristics and tolerability profile of women in labor managed with camylofin dihydrochloride injection - Taneja, Vinita K.; Telang, Milind A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To determine the clinical and obstetric characteristics and tolerability profile of pregnant women in the active phase of labor who were managed with Camylofin dihydrochloride injection. Methods: Retrospective data of 210 full-term pregnant women in the active phase of labor who were managed with Camylofin injection doses of 50 mg, 50+25 mg and 50+50 mg were considered in the study. The comparative effectiveness of 3 doses was evaluated using independent T-test and ANOVA at 5% level of significance. Results: The overall mean maternal age was 25.4 (±4.14) years with mean gestational age of 38.8 (±1.04) weeks. In total, 77.1% (n=162) of patients needed 50 mg dose of Camylofin injection for adequate cervical dilatation, and additional doses of 25 mg or 50 mg were required in 16.7% (n=35) and 6.2% (n=13), of patients, respectively to accelerate the labor. The mean cervical dilatation rates increasing dose viz 2.8 cm/hr, 4.1 cm/hr and 2.9 cm/hr, respectively. The adverse events were 14.8% (n=23) in 50 mg arm, 34.3% (n=12) in 50+25 arm and 69.0% (n=9) in 50+50 arm. Of the total, 34 events (50.0%) were related to Camylofin dihydrochloride injection, i.e. ADRs. The means of cervical dilation rate, active phase duration and total duration of labor were statistically significant (p-value <0.001) for 50 mg versus 50+25 mg. Conclusions: The study infers Camylofin injection usage with consideration of dose escalation in the routine clinical management of labor. Both mother and neonate had shown comparable tolerability profile across the three dosage arms with minimal events.